Deep Learning Technology Implementation in Equivalency Education: A Study of Teacher Readiness and Students' Critical Thinking Enhancement in West Java, Indonesia - Derry Nugraha; Edy Rachmadio; Fatra Syahlan (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Critical thinking deficiency among equivalency education students in Indonesia represents an urgent challenge demanding innovative solutions. This study investigates the impact of deep learning technology on critical thinking skills among Package B and C students in West Java, Indonesia, with teacher readiness as a moderating variable. A quasi-experimental pre-test post-test control group design was employed, involving 240 students from 30 non-formal education centers randomly allocated to experimental (n=120) and control (n=120) groups, along with 60 teachers. The experimental group received instruction through a deep learning-based AI platform, while the control group used conventional methods. Critical thinking was measured using the Indonesian-adapted Watson-Glaser Critical Thinking Appraisal, and teacher readiness was assessed through a validated questionnaire. Results showed the experimental group achieved a 20.2% improvement in critical thinking scores (d=1.65), significantly higher than the control group (5.2%; d=0.41). Teacher readiness was the strongest predictor of implementation success (β=0.45), followed by implementation duration, infrastructure support, and student motivation (R²=0.68). These findings demonstrate that deep learning technology effectively enhances critical thinking in non-formal education when supported by adequate teacher preparation, supporting the strategic adoption of AI platforms for educational equity